In vitro comparison of laser fluorescence performance with visual examination for detection of occlusal caries in permanent and primary molars - Rodrigues, Jonas A. [UNESP]; Diniz, Michele B. [UNESP]; Josgrilberg, Erika B. [UNESP]; Cordeiro, Rita C. L. [UNESP] (Springer London Ltd, 2009)
The aim of this study was to compare the performance of the DIAGNOdent 2095 with visual examination for occlusal caries detection in permanent and primary molars. The sample comprised 148 permanent human molars and 179 primary human molars. The samples were measured and visually examined three times by two examiners. After measurement, the teeth were histologically prepared and assessed for caries extension. Sensitivity, specificity, accuracy and area under the receiver operating characteristics (ROC) curve were calculated. Intra-class correlation (ICC), unweighted kappa and the Bland and Altman method were used to assess inter- and intra-examiner reproducibility. DIAGNOdent showed higher specificity and lower sensitivity than did visual examination. The ICC values indicated an excellent agreement between the examinations. Kappa values varied from good to excellent for DIAGNOdent but from poor to good for visual examination. In conclusion, the DIAGNOdent may be a useful adjunct to conventional methods for occlusal caries detection.
Keywords: Primary teeth; Permanent teeth; Laser fluorescence; DIAGNOdent; Visual examination; Occlusal caries detection